Implementasi Pendekatan Humanistik dan Behavioristik dalam Meningkatkan Motivasi Belajar Santri di Pondok Pesantren Al Hidayah Basmol - Yokha Latief Ramadhan; Aenurafiq (Medan Resource Center, 2025)
This study aims to describe the implementation of educational psychology theories, particularly learning motivation, humanistic, behavioral, and cognitive theories, in character development and the enhancement of students’ learning motivation at Al Hidayah Basmol Islamic Boarding School. The study employed a qualitative descriptive approach to gain an in-depth understanding of educational practices within the pesantren environment. Data were collected through observation, interviews, and documentation involving students, teachers (ustadz), and boarding school administrators. The collected data were analyzed using interactive data analysis techniques, including data reduction, data display, and conclusion drawing. The findings revealed that students demonstrated a high level of learning motivation, particularly in religious subjects such as Qur’an memorization (tahfiz), Islamic jurisprudence (fiqh), Qur’anic exegesis (tafsir), and moral education (akhlaq). This motivation was influenced by internal factors, including sincere intentions to worship and seek the pleasure of Allah SWT, as well as external factors such as support from teachers, parents, and a conducive boarding school environment. The teachers applied a humanistic approach through empathetic interactions and individualized guidance, while behavioral principles were implemented through educational reward and punishment systems. Furthermore, cognitive learning theory was reflected in the use of concrete instructional methods and learning styles adapted to students’ characteristics, including visual, auditory, and kinesthetic preferences. Character values such as honesty, responsibility, cooperation, and discipline were emphasized throughout the educational process. Relationships among students, teachers, and administrators were developed in a warm, family-oriented atmosphere while maintaining educational authority. The study concludes that the integration of psychological approaches creates a harmonious educational climate, strengthens students’ moral character, and sustainably enhances their learning motivation.